Teaching, reading in mathematics : A supplement to teaching reading in the content areas - Barton, Mary Lee.; Heidema, clare (Parker Road : McREL, 2002)
Teaching Reading in Mathematics' explores the distinct challenges of reading in the context of mathematics. The authors ... begin by examining what research says about the role of the reader, the role of climate, and the role of text features for reading in mathematics. Further, they explain strategic processing as effective readers of mathematics use it and discuss strategic teaching in mathematics that incorporates reading to learn mathematics. Many of the books principles derive from the latest recommendations of the National Council of Teachers of Mathematics
Include bibliography.
Keywords: Reading (Elementary); Reading (Secondary); Mathematics -- Terminology